2006
DOI: 10.1007/s00395-006-0605-4
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF does not improve systolic function in a rat model of acute myocardial infarction

Abstract: These data clearly shows that G-CSF treatment was unable to prevent cardiac remodeling or to improve cardiovascular function in a rat model of acute myocardial infarction, by permanent LAD ligation, despite bone marrow stem cell mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…In the present study, intravenous infusion of MSCs with G-CSF showed no improvement in all functional and histomorphological parameters. Several more recent experimental studies seem to support our conclusions [33,34]. In the clinical setting, administration of G-CSF (10 μg/kg/day for 5 days) to patients with advanced coronary artery disease and recurrent ischemia increased circulating CD34 + / CD133 + cells but without objective evidence of cardiac benefit [35].…”
Section: Discussionsupporting
confidence: 49%
“…In the present study, intravenous infusion of MSCs with G-CSF showed no improvement in all functional and histomorphological parameters. Several more recent experimental studies seem to support our conclusions [33,34]. In the clinical setting, administration of G-CSF (10 μg/kg/day for 5 days) to patients with advanced coronary artery disease and recurrent ischemia increased circulating CD34 + / CD133 + cells but without objective evidence of cardiac benefit [35].…”
Section: Discussionsupporting
confidence: 49%
“…MI was induced by left coronary artery (LCA) ligation as previously described [13] in 60 rats. Briefly, rats were anesthetized with isoflurane (Merck) and after exposing the heart, LCA were permanently occluded with a 6-0 silk suture, then the chest was closed with silk stitch and rats were allowed to recover.…”
Section: Animals and MImentioning
confidence: 99%
“…Although many studies observed the beneficial effects of G-CSF treatment before [6,7,9] and after MI [8,[10][11][12] controversy still exists. In this context, Werneck-de-Castro et al [13] demonstrated that the administration of high doses of G-CSF early after MI failed to improve cardiac function at rest or under exercise stress in rats. Similar negative results were observed in mice [14], rats [15], porcine [16] and baboons [17].…”
Section: Introductionmentioning
confidence: 97%
“…The present study by Liu et al also demonstrates that early G-CSF treatment (1 h post-MI) may exacerbate structural and mechanical deficits post-MI since hemodynamic parameters were depressed and the ventricular expansion index was augmented. In this scenario, our laboratory failed to demonstrate any beneficial effect of G-CSF either in the acute [20] or during the chronic phase of MI [21]. Considering the number of publications, it seems that the interest in this field of research has declined after a series of negative results in pre-clinical studies until 2006 (Fig.…”
Section: Pre-clinical Experimentsmentioning
confidence: 91%